Delamination of layered double hydroxides in polar monomers: new LDH-acrylate nanocomposites. - O'Leary, S; O'Hare, D; Seeley, G (2002)
The layered double hydroxide Mg2Al(OH)6(C12H25SO4) was delaminated to give high levels of inclusion in acrylate monomers; subsequent polymerisation of the monomers containing the LDH dispersion gave polyacrylates with the inorganic component still in the delaminated form.